RE-AIM Evaluation Plan for Washington State Innovation Models Project. Issue 2 (April 2020) - Grembowski, David; Conrad, Douglas A.; Naranjo, Diana; Wood, Suzanne; Coe, Norma B.; Kwan-Gett, Tao; Baseman, Janet
Abstract : The State of Washington received a State Innovation Models (SIM) $65 million award from the federal Centers for Medicare & Medicaid Services to improve population health and quality of care and reduce the growth of health care costs in the entire state, which has over 7 million residents. SIM is a "complex intervention" that implements several interacting components in a complex, decentralized health system to achieve goals, which poses challenges for evaluation. Our purpose is to present the state-level evaluation methods for Washington's SIM, a 3-year intervention (2016-2018). We apply the RE-AIM (reach, effectiveness, adoption, implementation, and maintenance) evaluation framework to structure our evaluation. We create a conceptual model and a plan to use multiple and mixed methods to study SIM performance in the RE-AIM components from a statewide, population-based perspective.